Meta Analysis: Relationship of Husband’s Knowledge and Support During Pregnancy with Antenatal Care (ANC) Visits by Pregnant Mothers - Rizka Yuli Wahyuni; ZairinNoor; Roselina Panghiyangan; Husaini; Meitria Syahadatina Noor (Institute of Medico-legal Publications Pvt Ltd, 2022)
Antenatal Care (ANC) is a health service by trained health workers for mothers during their pregnancy, which must be carried out routinely, according to standards and in an integrated manner. ANC services are indispensable and recommended for pregnant women in order to maintain the health of the mother and fetus during pregnancy, detect and treat abnormalities early and prepare the mother for safe delivery. In fact, there are still many pregnant women who do not access ANC services according to standards, so this situation can contribute to morbidity and mortality rate (MMR).The research was conducted in November 2020 – March 2021 by searching for secondary data from two electronic databases, namely Google Scholer and Pubmed (2015 to 2020). Studies were selected through the PRISMA protocol and critically assessed using JBI’s Critical Appraisal Tool. Test for heterogeneity, summary effect and publication bias using the JASP application version 0.14.1. Odd ratio with 95% confidence level (CI) was used to calculate the effect size. From the selected data, the husband’s knowledge and support factors have quite a lot of differences in research results, so it is necessary to re-analyze the relationship of husband’s knowledge and support during pregnancy with ANC visits by pregnant women to produce more accurate conclusions. Based on the inclusion criteria, there were 17 studies that could be included in the meta-analysis, with 3.956 respondents from Indonesia, Ethiopia and Vietnam. Homogeneous data with the combined OR value of knowledge of pregnant women with ANC visits is 2,48 (95% CI; 2,01-3,03) and the relationship of husband’s support during pregnancy with ANC visits is 2,03 (95% CI; 1,65-2,51), and there are publications biased. This meta-analysis confirms that there is a significant positive relationship between husband’s knowledge and support during pregnancy and ANC visits.